The Marcel Marceau alphabet book. - Mendoza, George; Greene, Milton H. (Garden City, N.Y. : Doubleday, 1970)
Photographs of pantomimist Marcel Marceau record his mimes of twenty-six words which represent objects or activities.
Keywords: Marceau, Marcel, -- 1923-2007.; Alphabet